Tecnologias limpas aplicadas ao tratamento de águas residuárias domésticas para reuso no semiárido - Lopes, Humbelina Silva Siqueira (2012)
The scarceness of water and the lack of sanitation services in rural environment is a reality of northeastern semi-arid, being indispensable the development of low cost technologies, with easy operation and high efficiency, in addition to being environmentally accepted by society. Considering that, this work intended to analyze the performance of mini-stations of domestic wastewater treatment for reuse in northeastern semi-arid regions. The experiments have been done at UFERSA s experimental areas in Mossoró RN, experiments I with grey water, experiment II with domestic sewage. Some procedures were made to analyze the mini-stations, they were the flow measurement and the characteristic determination: hydrogen-ion potential (pH), electrical conductivity (EC), turbidity (TB), total coliforms (TC), thermotolerant coliforms (ThC), chemical oxygen demand (COD), biochemical oxygen demand (BOD), total solids (TS), suspended solids (SS), total phosphorus (P-total), total nitrogen (N-total), oil and grease (OG) and nitrate (NO3-). The experiments were set in the Completely Randomized Design with four repetitions and four treatments (treatment levels). The analysis of variance was done to 1 and 5 % of probability, the averages were compared using Turkey s test at 5 % of probability. The results evidence that the applied treatment at experiments I caused significant removals of the characteristics TB, TC, ThC, COD, BOD, TS, SS, P-total and OG; and by the average level of 29.22 MJ m-2 d-1 the obtained average removal was 98.82 % at ThC population. At experiments II significant removals occurred of TB, TC, ThC, COD, BOD, SS, P-total, NO3- and OG; and with average solar radiation of 27.81 MJ m-2 d-1, it occurred an average removal in ThC population of 99.98 %. The mini-stations of domestic wastewater treatment enable the effluent the microbiological quality that follows the national guidelines to fertigation of crops when not eaten raw